Geological features and the Paleoproterozoic collision of four Archean crustal segments of the São Francisco Craton, Bahia, Brazil. A synthesis - Johildo S. F. Barbosa (Anais da Academia Brasileira de Ciências, 2002)
Recent geological, geochronological and isotopic research has identified four important Archean crustalsegments in the basement of the São Francisco Craton in the State of Bahia. The oldest Gavião Block occursin theWSW part, composed essentially of granitic, granodioritic and migmatitic rocks. It includes remnantsof TTG suites, considered to represent the oldest rocks in the South American continent (∼ 3, 4Ga) andassociated Archean greenstone belt sequences. The youngest segment, termed the Itabuna-Salvador-CuraçáBelt is exposed along the Atlantic Coast, from the SE part of Bahia up to Salvador and then along a NE trend.It is mainly composed of tonalite/trondhjemites, but also includes stripes of intercalated metasedimentsand ocean-floor/back-arc gabbros and basalts. The Jequié Block, the third segment, is exposed in the SESSWarea, being characterized by Archean granulitic migmatites with supracrustal inclusions and severalcharnockitic intrusions. The Serrinha Block (fourth segment) occurs to the NE, composed of orthogneissesand migmatites, which represent the basement of Paleoproterozoic greenstone belts sequences. During thePaleoproterozoic Transamazonian Orogeny, these four crustal segments collided, resulting in the formation ofan important mountain belt. Geochronological constrains indicate that the regional metamorphism resultingfrom crustal thickening associated with the collision process took place around 2.0 Ga.